2002
DOI: 10.2307/4300619
|View full text |Cite
|
Sign up to set email alerts
|

The Fortification and Palace of Northern Gonur

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. British Institute of Persian Studies is collaborating with JSTOR to digitize, preserve and extend access to Iran.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…This remarkable variability in handmade coarseware ceramics has so far not been discussed in the literature for this period and region. At present, it is possible to say that the great variability in the paste attributes of coarseware ceramics points to a non-centralized and non-specialized production regime, unlike the wheel-made ceramics found throughout the Murghab alluvial fan that seem to have been standardized, and often produced in mass quantities in large kilns like those found at Gonurdepe (Sarianidi and Puschnigg 2002). The Ojakly coarsewares were not fired in the carefully controlled atmosphere of a kiln.…”
Section: Contextual Differences In Ceramicsmentioning
confidence: 92%
See 1 more Smart Citation
“…This remarkable variability in handmade coarseware ceramics has so far not been discussed in the literature for this period and region. At present, it is possible to say that the great variability in the paste attributes of coarseware ceramics points to a non-centralized and non-specialized production regime, unlike the wheel-made ceramics found throughout the Murghab alluvial fan that seem to have been standardized, and often produced in mass quantities in large kilns like those found at Gonurdepe (Sarianidi and Puschnigg 2002). The Ojakly coarsewares were not fired in the carefully controlled atmosphere of a kiln.…”
Section: Contextual Differences In Ceramicsmentioning
confidence: 92%
“…1). Also in this period, the Murghab alluvial fan became home to preplanned, fortified urban complexes with geometric layouts and monumental public architecture, specialized production areas for pottery, and small crafts that grew into a distinctly new tradition (Kohl 2007;Hiebert 1994a;Sarianidi 1981Sarianidi , 1993Sarianidi , 2006Sarianidi , 2008Sarianidi and Puschnigg 2002). Shortly thereafter, the first archaeological evidence for another population appears in the form of a few ceramic sherds of different manufacture, vessel form, and decoration, but it is not until the Late Bronze Age (1950-1500 B.C.…”
Section: Introductionmentioning
confidence: 99%
“…A few terracotta pipes have been identified at Gonur North (Sarianidi and Dubova, 2012), Togolok 1, and Togolok 21 (Hiebert, 1994). It has been suggested that these pipes (created by a series of interconnected terracotta conical tubes) were used to fill the pools found at the palace-temple complex and also as part of the drainage system of the palace at Gonur North (Sarianidi and Puschnigg, 2002;Sarianidi and Dubova, 2012). No water basins or artificial canal like those found at Gonur (Sataev, 2008;Sarianidi and Dubova, 2012), however, have been uncovered at Togolok 1 (Cerasetti et al, in press a).…”
Section: Legumesmentioning
confidence: 99%
“…330 × 460 m, includes the socalled Monumental Palace and its subsidiary buildings, several temples and ritual areas, the so-called Royal Necropolis, and two major and several smaller water reservoirs, all dating from ca. 2400 to 1900 BCE (Sarianidi, 2002b(Sarianidi, , 2005Vidale, 2017: 9, Table 1). Most of the elephant ivory objects found at Gonur Depe came from funerary structures that can be dated to the last occupational phase of this area, which according to material culture comparanda are considered contemporaneous to the upper levels of Altyn Depe, in southwestern Turkmenistan, and Mohenjo-Daro, in the Sindh province of present-day Pakistan (Table 1).…”
Section: Gonur Depe and The Indus Civilizationmentioning
confidence: 99%